Program Saring Sebelum Sharing untuk Meningkatkan Kemampuan Verifikasi Hoaks Siswa SMP - Wayan Wirayana; Hans prismanta sembiring; Muhammad aldi nur haq; Zeskind Loveressaa; Supriyadin Supriyadin; Ilham Muhammad Ridho (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The rapid growth of digital media has increased adolescents' access to information while also exposing them to misinformation and hoaxes. Limited information verification skills highlight the need for practical digital literacy programs. This article describes the dissemination of the "Saring Sebelum Sharing" program through the Information Detective approach to improve hoax verification skills among junior high school students. The program involved 15 students at SMP Karitas Ngaglik through an interactive workshop covering digital literacy, hoax identification, and hands-on practice using Google Lens and reverse image search. Program effectiveness was evaluated using pre-test and post-test assessments. The results showed an increase in participants' understanding from 80% to 86.7%. Participants also demonstrated active engagement and were able to apply information verification techniques independently. These findings indicate that the Information Detective approach is an effective digital literacy strategy for fostering a "Filter Before Sharing" culture among junior high school students.